Bioinspired selective synthesis of liquid-crystalline nanocomposites: formation of calcium carbonate-based composite nanodisks and nanorods. Issue 6 (14th May 2020) - Nakayama, Masanari; Kajiyama, Satoshi; Kumamoto, Akihito; Ikuhara, Yuichi; Kato, Takashi
Abstract : Colloidal nanodisk liquid-crystalline composites consisting of an acidic polymer and CaCO3 are developed. Selective synthesis of nanodisk and nanorod is achieved by biomineralization-inspired approaches. Abstract : Here we report new organic/inorganic hybrid colloidal liquid crystals that consist of colloidal calcium carbonate (CaCO3 )/poly(acrylic acid) (PAA) hybrid nanodisks. We selectively synthesized anisotropic liquid-crystalline CaCO3 -based nanodisk and nanorod composites in water/methanol mixtures, which formed discotic and calamitic nematic liquid crystals in their colloidal dispersions, respectively. The vaterite nanodisks and calcite nanorods were selectively synthesized in methanol-rich and water-rich solutions, respectively. The observation of these materials with transmission electron microscopy clarified the atomic-scale structures of these nanodisks and nanorods, revealing the self-organized CaCO3 /PAA hybrid structures with the ability to form colloidal liquid crystals. The liquid crystals were prepared under mild and aqueous conditions by methods using acidic polymers inspired by the biomineralization process. The present approach provides new insights into the design of organic/inorganic hybrid colloidal liquid crystals and development of environmentally friendly functional hybrid materials.